2003
DOI: 10.1002/mrm.10430
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of myocardial blood volume and water exchange: Theoretical considerations and in vivo results

Abstract: The measured signal response in contrast-enhanced myocardial perfusion imaging has been shown to be affected by the rate of water exchange between the intravascular and extravascular compartments, the effect being particularly significant when intravascular contrast agents are used. In the present study, the T 1 relaxation rates were measured in eight pigs in blood and myocardium using a Look-Locker sequence after repeated injections of the intravascular contrast agent NC100150. The selection of myocardial reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 25 publications
3
33
1
Order By: Relevance
“…The R 1 measurements in perfused myocardium before CA administration (R 1 ϭ 912 Ϯ 55 msec -1 ) are consistent with previous studies in which R 1 was found to be 860 msec -1 and 930 msec -1 in pigs (25,27), and 840 msec -1 in humans (28).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The R 1 measurements in perfused myocardium before CA administration (R 1 ϭ 912 Ϯ 55 msec -1 ) are consistent with previous studies in which R 1 was found to be 860 msec -1 and 930 msec -1 in pigs (25,27), and 840 msec -1 in humans (28).…”
Section: Discussionsupporting
confidence: 91%
“…Parametric R 1 maps and corresponding 2 error maps (25) (Fig. 1) were calculated from a nonlinear least-squares fit of the Look-Locker data to the equation SI(TI) ϭ ␤ ϫ |(1 -2e -R1ϫTI )| ϩ K, where || denotes the modulus, ␤ and K are fitting constants, and R 1 ϭ 1/T 1 is the model parameter to be determined (26).…”
Section: Mr Image Evaluationmentioning
confidence: 99%
“…Similarly, transendothelial exchange rates have been estimated to be 1-6 s -1 in myocardium (18,35). Several approaches have been proposed to account for the effect of water exchange on the relaxation kinetics (34,36,37), although a consensus has yet to emerge on how to best account for these effects and how to balance the need for additional model parameters and the limited precision of the measurements. In the worstcase scenario, the consequence of assuming fast exchange where it does not exist is the underestimation of v p and the overestimation of K trans (17,38).…”
Section: Discussionmentioning
confidence: 99%
“…Our 99m Tc vs. CMR values are fairly consistent, however, this would explain any slight overestimation for epicardial MBV with our CMR method. Thirdly, the water exchange effect was not accounted for in our deconvolution model calculation of MBV (32). This is particularly important when an intravascular contrast agent is used.…”
Section: Limitationsmentioning
confidence: 98%